Cheerleading for fun! - Gruber, Beth. (Minneapolis, MN : Compass Point Books, 2004)
An introduction to cheerleading, presenting the history of this activity, advice on tryouts, the necessary skills and techniques involved, information on camps and competitions, and more.
Includes bibliographical references (p. 47) and index.
5.7
3-6
Keywords: Cheerleading -- Juvenile literature; Cheerleading; Cheerleading